Educational Status, Aware Ness and Sources of Information of Osteoporosis Patients - Yeşim Gökçe Kutsal; Ayçe Atalay; Şule Arslan; Aynur Başaran; Ferhan Cantürk; Abdullan Cindaş; Merih Eryavuz; Jale İrdesel; Kıymet İkbal Karadavut; Yeşim Kirazlı; Dilşad Sindel; Kazım Şenel; et al. (Galenos Yayinevi, 2002)
Osteoporosis is one of the major public health problems. Higher prevalence of most chronic diseases has been encountered in less educated subjects. Aim of this study was to assess educational status, knowledge and sources of information among subjects with osteoporosis. A multicentered trial involving 10 centers was carried out. Patients with bone mineral densities below -2.5 standard deviations either in femoral or lomber region were included in the study. Age, sex, height, weight, educational status, clothing style, drugs used for osteoporosis, age at menarche, age at menopause, type of menopause, oral contraception, presence of chronic disease, smoking status, physical activity level, calcium intake, knowledge about osteoporosis and sources of information was gathered using a questionnaire. 54 % of our patients had knowledge about osteoporosis. Doctors were the most commonly utilized source of information (56.8%). Patients were divided into 3 groups according to educational status: less than 5 years (392 patients, 68.9 %), 6 to 8 years (53 patients, 9.3 %) and more than 9 years (124 patients, 21.8 %). Body mass index, presence of obesity, smoking status and physical activity levels were significantly different between the groups. Knowledge about osteoporosis was compared according to years of formal education. 43.7 % of patients with formal education less than five years, 62.3 % of patients with formal education 6-8 years and 83.7 % of patients with formal education more than 9 years had knowledge about osteoporosis. Knowledge about osteoporosis was significantly different between groups. Patients within different geographical regions were compared. Educational status, clothing style, smoking status, activity levels, calcium intake and knowledge about osteoporosis was found to be statistically significantly different between the groups. Education of both patients and doctors will lead to better understanding of concept of "bone health".